Direct and indirect influences of intercrops on the coconut defoliator Opisina arenosella - Shameer, K.S.; Nasser, M.; Mohan, Chandrika; Hardy, Ian C.W. (Springer, 2018)
Coconut palm (Cocos nucifera) infestation by Opisina arenosella (Lepidoptera: Oecophoridae) in the Indian sub-continent may occur in November to May each year in the same or adjoining areas of plantations. Parasitoids of O. arenosella may also be consistently present at these times. During other periods, pests and/or parasitoids could be maintained on intercrops that are commonly grown throughout the year. Field surveys of 54 intercrop species in Kerala, India, found that O. arenosella attacks banana, but not others, while laboratory screening showed that O. arenosella can mature on jack fruit, cashew and oil palm. Larvae of 20 lepidopteran species found on intercrops were screened for use by Goniozus nephantidis (Hymenoptera: Bethylidae), a larval parasitoid of O. arenosella, which oviposited on two species but its offspring failed to mature. Thirteen intercrop herbivore species were screened for use by Brachymeria nosatoi (Hymenoptera: Chalcididae), a pupal parasitoid of O. arenosella, which completed development on the pyralids Herculia nigrivita, Syllepte derogata and Psara basalis. Further, connectance trophic webs were compiled using prior field records of coconut, 33 species of intercrops, 58 species of lepidopteran herbivores and 29 species of primary parasitoids. Both laboratory and literature evidence suggests that populations of O. arenosella are unlikely to be maintained by feeding on intercrops or strongly influenced by direct competition with other lepidopterans but are likely to be affected by sharing parasitoids. Intercrop herbivores have clear potential for maintaining parasitoids of O. arenosella and we recommend thirteen plant species as intercrops that should aid in conservation biocontrol.